Enhancing Customer Experience and Business Innovation through Digital Platforms in Southeast Asia - Palma Juanta; Sandy Setiawan; Hetilaniar; Brigitta Callula (Pandawan, 2026)
The rapid expansion of digital platforms across Southeast Asia has accelerated the emergence of interconnected digital ecosystems that integrate multiple services, partners, and data-driven interactions, fundamentally reshaping customer expectations and competitive dynamics in the region. This study aims to examine how ecosystem oriented digital platforms enhance customer experience and foster business model innovation by analyzing the influence of ecosystem capabilities, service integration, and value co-creation. Using a quantitative approach, data were collected from 378 active users of digital platforms across Indonesia, Malaysia, Vietnam, Thailand, and the Philippines, and analyzed using Structural Equation Modeling with Partial Least Squares (SEM–PLS) to evaluate relationships among key variables. The findings indicate that strong ecosystem capabilities significantly improve customer experience through seamless integration, personalization, and multi-stakeholder collaboration, while customer experience also mediates the relationship between ecosystem capabilities and business model innovation. Furthermore, ecosystem oriented platforms demonstrate greater agility and value creation potential compared to single-service platforms. These results underscore the strategic importance of digital ecosystems in driving superior customer experience and enabling sustainable business model innovation in Southeast Asia, offering valuable implications for digital firms, startups, and policymakers to strengthen regional digital transformation.